Prenatal ultrasound diagnosis and prognosis of persistent left superior vena cava: a 10-year retrospective cohort study at a single center in China - Wei, Ronghui; Gong, Jingyi; Ling, Wen; Wu, Qiumei; Lyu, Guorong; Wang, Yu; Weng, Zongjie (Frontiers in Medicine, 2026)
ObjectiveTo describe the prenatal ultrasound characteristics of persistent left superior vena cava (PLSVC) in fetuses and its correlation with related malformations, chromosomal abnormalities, and clinical outcomes.MethodsA 10-year retrospective analysis of the clinical and ultrasound data of 898 fetuses diagnosed with PLSVC at our center was conducted. Ultrasound characteristics of PLSVC type were summarised systematically, and incidence rates of abnormalities and pregnancy outcomes of PLSVC types were determined.ResultsDiagnosing PLSVC requires the 4CV, 3VV and 3VT views, while auxiliary classification requires parasagittal and innominate vein views. PLSVC ultrasound features include coronary sinus dilation and an additional vascular cross-section on the left side of the pulmonary artery. Types I and II PLSVC involved 94.2% vs. 5.8% of cases, respectively. Type I PLSVC had lower incidence of abnormalities (70.3%) than Type II (100%; p < 0.001) and higher birth rates (63.5% vs. 7.7%; p < 0.001). However, they differed non-significantly in incidence of chromosomal abnormalities (p > 0.05). Of fetuses, 28.0 and 72.0% had isolated and non-isolated PLSVC, respectively. Lower incidence of chromosomal abnormalities occurred in fetuses with isolated PLSVC (7.8%) than that in non-isolated PLSVC (22.0%; p < 0.05). Among the non-isolated group, the subgroup with coexisting cardiac and extracardiac abnormalities had the highest incidence of chromosomal abnormalities (39.5%; p < 0.005). Higher live birth rate occurred for fetuses with isolated PLSVC (99.2%) than for non-isolated PLSVC (45.1%; p < 0.001).ConclusionMultifaceted prenatal ultrasound is valuable for classifying and categorizing fetal PLSVC. Classifying PLSVC and assessing accompanying abnormalities is key to determining prognosis. Type II or non-isolated PLSVC, when accompanied by intracardiac and extracardiac abnormalities, requires enhanced genetic testing and multidisciplinary management. Contrariwise, Type I or isolated PLSVC has good prognosis.